The constitutional duty of the Russian Federation’s President to sign a law - Antsiferov, Nikolay V. (Opción, 2020)
The article examines the legislative powers of the President of the Russian Federation, including the President’s obligation to sign and promulgate the law, as well as the right to veto it via comparative qualitative research methods. As a result, the topic of specifying the limits of state activity involves highlighting the various negative "undersides" of the state mechanism. In conclusion, in order to reduce the tendency of vetoed laws, the Federal Assembly should at all stages of the legislative process pay more attention to the President’s position on each bill